Bentuk Variasi Sosiolek Dalam Transaksi Jual Beli Di Pasar Molotabu Kecamatan Kabila Bone Kabupaten Bone Bolango: Penelitian - Avriliawati A. Nihali; Sayama Malabar; Muslimin (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to describe the forms of sociolect variation used in buying and selling transactions at Molutabu Market and identify the factors behind the emergence of these variations. This study uses a qualitative descriptive approach with data collection techniques in the form of observation, recordings, and interviews. The data obtained are analyzed based on the theory of language variation and sociolect in sociolinguistic studies. The results show that in buying and selling interactions at Molutabu Market, Kabila Bone District, Bone Bolango Regency, there are nine forms of sociolect variation, namely acrolect, basilect, slang, jargon, colloquial, argot, ken, vulgar, and slang. These variations arise due to differences in age, gender, occupation, education, and social status between speakers. In addition, the use of Indonesian mixed with the Gorontalo dialect indicates linguistic adjustments to facilitate communication and build familiarity between sellers and buyers. Referring to the results of the study, it can be concluded that sociolect variation in buying and selling transactions not only represents language styles, but also reflects the social structure and relationships between individuals in the local community. Language becomes a tool to adapt to the social context and maintain the cultural identity of market society